2020
DOI: 10.1111/1759-7714.13541
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of immune‐related adverse events of immune checkpoint inhibitor therapy in cancer patients

Abstract: Background Immune checkpoint inhibitors (ICIs) have significant clinical efficacy in the treatment of non‐small cell lung cancer (NSCLC); however, the incidence of immune‐related adverse events (irAEs) of up to 50% has prevented their widespread use. With the increase in the use of ICIs alone or as combination therapy, clinicians are required to have a better understanding of irAEs and be able to manage them systematically. In this study, we aimed to assess the incidence of irAEs associated with ICIs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 147 publications
(247 reference statements)
3
57
0
1
Order By: Relevance
“…Immune checkpoint inhibitors (ICI) are associated with a broad spectrum of unique immune-mediated toxicities, requiring expert management, as these toxicities may occasionally be life threatening [144]. Immune-mediated toxicities can affect most organ systems and are believed to arise from autoimmune inflammatory complications of ICI treatment.…”
Section: Immune Related Toxicitymentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICI) are associated with a broad spectrum of unique immune-mediated toxicities, requiring expert management, as these toxicities may occasionally be life threatening [144]. Immune-mediated toxicities can affect most organ systems and are believed to arise from autoimmune inflammatory complications of ICI treatment.…”
Section: Immune Related Toxicitymentioning
confidence: 99%
“…However, ICI, as well as some other immunotherapy approaches such as cytokine administration, can stimulate the immune system non-specifically, and hence, they can also trigger the activation of self-reactive lymphocytes. Therefore, immune-related adverse effects (irAEs) such as skin lesions, colitis, and thyroiditis might occur due to an autoimmune attack, limiting the clinical benefit of these treatments [ 6 ]. As these therapies are finding their place in the clinic rather quickly, evading irAEs and stratifying patients at a risk of developing immune toxicities are becoming particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of safety index, the severity of adverse event was divided into five grades. The most common adverse reactions were reactive capillary hyperplasia (77.4%), elevated aspartate aminotransferase (19.0%), elevated alanine aminotransferase (17.5%), hypothyroidism (16.7%), fatigue (15.3%), anemia (14.1%), elevated serum bilirubin (11.5%), proteinuria (10.8%), fever (10.4%), and leukopenia (10%) (27,28). Through metaanalysis, we found that when the grade of adverse events was > 2, the incidence of single use was lower than combination therapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%